Uma análise ontológica do Gestell: a problematização da técnica moderna e da entificação do ser - Leite, Maria Risonete Simplicio (2009)
This search is intended to analyze a modern essential techines, Gestell, and the identify problem of the human being. The modern technique question in central thought themes of Martin Heidegger who provide guidance for a question getting to human being. To Heidegger the occidental metaphysic story to agree with forgetfulness of the human being since your Greek foundation, on asked in considerate his limits to identify. The human s forgetfulness enterprising with the occidental metaphysic, result in a formulation of the calculate thought into a modern technique that reached dimension planet. The technique s era to represent a finish of metaphysic in make sense to find some conditions for yours extreme possibility being reach. So that represent the last story of the forgetfulness too, in once the human being meet distant to statute the identify and all people are questionable in way disponibility and calculus. The dissertation s running look up therefore a principal definitions presents in Heidegger s thought so get a comprehension an essential s panorama as base a technique question.